The Construction of Islamic Law on Marriage: A Normative Study of Rights, Harmony, and Its Limits - Muhammad Husni Abdulah Pakarti; Wahyudi Wahyudi; Ah. Fathonih; Fauzan Ali Rasyid; Husain Husain (al-Battar: Jurnal Pamungkas Hukum, 2025)
Marriage in Islam is a social and spiritual institution that has a strong legal dimension. Islamic law regulates marriage comprehensively, starting from the pillars and conditions, objectives, to the annulment of marriage. Understanding the concept of Islamic marriage law is very important to ensure the continuity of family life in accordance with Islamic law and moral values. This research uses a qualitative-descriptive approach with a library research method. Data were collected through a review of primary and secondary sources, such as the Qur'an, hadith, classical and contemporary fiqh books, as well as Islamic legal literature and relevant legislation, including the Compilation of Islamic Law (KHI). It was found that the law of marriage in Islam includes five kinds of laws based on individual conditions: obligatory, sunnah, permissible, makruh, and haram. A valid marriage according to Islam must fulfill five main pillars, namely the prospective husband, prospective wife, guardian, two witnesses, and ijab qabul. The rights and obligations of husband and wife are regulated proportionally to maintain family harmony. Islam also establishes prohibitions on marriage in order to maintain the sanctity of the relationship and accommodate the resolution of household conflicts through divorce, khulu', and fasakh. The concept of marriage law in Islam emphasizes the importance of justice, responsibility, and protection of the human rights of each partner. These values have high relevance in the dynamics of modern life and become a strong normative foundation in the formation of a sakinah, mawaddah, wa rahmah Muslim family. In addition, the flexibility of Islamic law in responding to social situations makes it relevant to be applied in pluralistic national and international legal systems.